Upregulation of heat shock protein 27 in metaplastic and neoplastic lesions of the endocervix. Issue 3 (1st April 2005) - El-Ghobashy, A. A.; Shaaban, A. M.; Innes, J.; Prime, W.; Herrington, C. S.
Abstract : Heat shock proteins (hsps) are molecular chaperones that are known to play a pivotal role in regulating intracellular homeostasis. hsp27 may have diagnostic and prognostic values for different gynecological malignancies. A cross-sectional analytical study was conducted at the Department of Pathology, The University of Liverpool, Liverpool, UK. Included in the study were 80 cervical glandular lesions of various histologic types, representing tuboendometrial metaplasia/endometriosis ( n = 19), cervical glandular intraepithelial neoplasia ( n = 33), and invasive adenocarcinoma ( n = 28). Paraffin-embedded sections were stained using a commercial mouse monoclonal anti-hsp27 antibody with prior pressure-cooking for antigen retrieval. Sections of 11 normal cervices were used as controls. The median percentage of cells expressing hsp27 in each group was calculated. Normal cervical glands showed minimal expression of hsp27 (median: 10%, interquartile ranges [IQ]: 5–15). Expression was significantly more widespread in tuboendometrial metaplasia/endometriosis (median: 35%, IQ: 15–80), cervical glandular intraepithelial neoplasia (median: 60%, IQ: 32–80), and invasive adenocarcinoma (median: 40%, IQ: 25–80) when compared with normal endocervix ( P = 0.007, <0.001, and 0.001, respectively). However, no significant difference in hsp27 protein expression was found between cervical glandular intraepithelial neoplasia and invasive adenocarcinoma. In invasive adenocarcinoma, hsp27 showed no correlation with tumor grade, lymph node involvement, and lymphovascular space invasion. Our data highlight early dysregulation of hsp27 expression in both metaplastic and neoplastic lesions of the cervix.